2019
DOI: 10.3390/pharmaceutics11110613
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of a Semi-Solid Dosage Form of Meglumine Antimoniate for Topical Treatment of Cutaneous Leishmaniasis

Abstract: Cutaneous leishmaniasis (CL) is treated with painful intralesional injections of meglumine antimoniate (MA). With the aim of developing an alternative topical treatment for CL, a gel-based formulation with 30% MA was prepared and its physicochemical properties, stability and rheological behavior were studied. The following were assessed: drug release on propylene hydrophilic membranes ex vivo human skin permeation, tolerance in healthy volunteers, cytotoxicity in three cell lines and anti-leishmanial activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 38 publications
(47 reference statements)
3
22
0
Order By: Relevance
“…The high porosity percentage of the AmB gel was corroborated by SEM images, which revealed undulating layers uniformly arranged and spaces between the layers, resembling holes or cavities. We reported similar levels of swelling, degradation and porosity in a previously characterized meglumine antimoniate Sepigel 305 ® [35].…”
Section: Discussionsupporting
confidence: 65%
“…The high porosity percentage of the AmB gel was corroborated by SEM images, which revealed undulating layers uniformly arranged and spaces between the layers, resembling holes or cavities. We reported similar levels of swelling, degradation and porosity in a previously characterized meglumine antimoniate Sepigel 305 ® [35].…”
Section: Discussionsupporting
confidence: 65%
“…Recently, TEWL values have been considered as criteria for SC integrity in CL clinical trials and they have shown decrease after treatment. 23,24 Then, greater amount of TEWL in lesions was predictable. SC hydration was increased after CL lesion treatment 23,24 and it was lower in lesions according to our results too, but the difference was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…TEWL evaluation showed greater amount in lesions. Recently, TEWL values have been considered as criteria for SC integrity in CL clinical trials and they have shown decrease after treatment 23,24 . Then, greater amount of TEWL in lesions was predictable.…”
Section: Discussionmentioning
confidence: 99%
“…The originality of the new formulations proposed are usually based on the selection of already approved excipients along with the active components, such as Montanide™ Petgel A as vaccine adjuvant [1], poly(vinyl alcohol) [2], Poloxamer 407™ [3], a combination of Capryol 90™, Peceol™ and Labrasol™ [4], dextran and maltodextrin [5], a combination of modified chitosan nanoparticles with a standardized extract of cultured Lentinula edodes mycelia (AHCC™) [6], ground calcium carbonate [7], poly (d,l-lactide-co-glycolide) 50:50 [8] and Sepigel 305™ [9]. Only in one paper [10], authors have synthesized a new material based on copolymers of poly(ethyleneglycol) and poly(ε-caprolactone) conjugated with retinol as drug vehicle.…”
mentioning
confidence: 99%
“…Berenguer et al developed and characterized a semi-solid gel dosage form of meglumine antimoniate for the topical treatment of cutaneous leishmaniasis [9]. The gel is easy to prepare and its main excipient is Sepigel 305™.…”
mentioning
confidence: 99%